Design of a Document Acquisition System Database - Balasubramanian, V. (Journal of Information and Knowledge, 1986)
A document acquisition control system database is designed to meet all functional requirements of acquisition process that are inherent with in frequent exceptions and also to handle the complex nature of bibliographical data efficiently towards integrated library house keeping procedures. Several function oriented physical Databases (PDBS) together with their logical relationships constitute the total Database, PDBS employ multi-list organization using appropriate access methods, viz., ISAM, DAM and ISAM/OSAM. The database is supported by recovery facilities and protected by security measures.